E-Book Development of Static Fluid Contents to Improve Students' Numeracy Literacy Competence - Muhammad Ziyyauddin Purwo Kartiko; Wahono Widodo; Madlazim Madlazim (Indonesia Approach Education, 2022)
This study aims to develop an E-Book on Static Fluid Content in Tutoring as an educational partner to improve students' numeracy literacy competence. E-Book development is carried out using the 4-D development model which consists of defining, designing, developing, and disseminating stages. The research instruments used were E-Book validation sheets and questions that were tested on material expert lecturers and media expert lecturers from Surabaya State University. The validation results show that the E-Book developed has a very valid quality, with a validity percentage of 97%. Aspects of presentation feasibility, content feasibility and linguistic feasibility in the E-Book as a whole meet the criteria of